Endodontic management of dens invaginatus of maxillary lateral incisor: A case report - Thapaliya, Ranjan; Joshi, Reema; Thapa, Asha; Shrestha, Reetu (Journal of Kathmandu Medical College, 2021)
Dens invaginatus is a developmental malformation of teeth with the enfolding of enamel and dentin into the pulp chamber and sometimes into the root that most commonly affects the maxillary lateral incisors. This anomaly may increase the risk of pulpal disease and can potentially complicate treatment due to its aberrant anatomy, thus posing a diagnostic challenge. Similarly, the incomplete elimination of the invagination and debridement may create dead space within the canal leading to the failures. This case reports the endodontic management of the Oehler’s type II Dens invaginatus.